EXPERIMENTAL AND THEORETICAL STUDY OF TWO-PHASE HEAT PIPE (Journal of Engineering, 2013)
In this study, thermal characteristics of a two-phase closed heat pipe were investigated experimentally and theoretically. A two-phase closed heat pipe (copper container, Fluorocarbon FC-72 (C6F14) working fluid) was fabricated to examine its performance under the effect of input heat flux range of 250–1253 W/m2 , 70% fill charge ratio and various tilt angles. The temperature distribution along the heat pipe, input heat to evaporator section, and output heat from condenser were monitored. A comprehensive mathematical model was developed to investigate the steadystate heat transfer performance of a two-phase closed heat pipe. A steady state analytical model, is presented to determine important parameters on the design of two-phase closed heat pipe, including temperature levels and heat transfer coefficients for condenser and evaporator. The experimental and simulation results of this work are found in good agreement. The experimental boiling heat transfer coefficients were compared with existing previously reported correlations.